2005
DOI: 10.1007/s11172-005-0386-1
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of aromatic aldehydes with β-dicarbonyl compounds in a catalytic system: Piperidinium acetate-1-butyl-3-methylimidazolium tetrafluoroborate ionic liquid

Abstract: Condensation of aromatic (heteroaromatic) aldehydes with 1,3 dicarbonyl com pounds under the 1 butyl 3 methylimidazolium tetrafluoroborate ([Bmim][BF 4 ]) ionic liq uid-piperidinium acetate catalytic system (0.2 equiv. of each component) in the absence of a solvent affords, depending on the structures of the reagents, 2 arylidene derivatives of methyl acetoacetate and acetylacetone, diethyl 2,4 bis(trifluoroacetyl) 3 phenylpentanedioate, or di methyl 2 aryl 4 hydroxy 6 oxocyclohexane 1,3 dicarboxylates. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Zlotin et al 416 The results of this study demonstrated that the condensation process was substantially affected by the ionic liquid. The authors affirmed that the product from the first step undergoes partial isomerization under the reaction conditions in the presence of NaHCO 3 and in an ionic liquid medium in a molar ratio of 1:0.2 (reactant/IL), which is more polar than DMF.…”
Section: Pyrimidines and Pyrimidinonessupporting
confidence: 48%
See 3 more Smart Citations
“…Zlotin et al 416 The results of this study demonstrated that the condensation process was substantially affected by the ionic liquid. The authors affirmed that the product from the first step undergoes partial isomerization under the reaction conditions in the presence of NaHCO 3 and in an ionic liquid medium in a molar ratio of 1:0.2 (reactant/IL), which is more polar than DMF.…”
Section: Pyrimidines and Pyrimidinonessupporting
confidence: 48%
“…The authors affirmed that the product from the first step undergoes partial isomerization under the reaction conditions in the presence of NaHCO 3 and in an ionic liquid medium in a molar ratio of 1:0.2 (reactant/IL), which is more polar than DMF . This compound is then transformed into the corresponding 3,4-dihydropyrimidin-2-(1 H )-ones 134 by regioselective N -alkoxycarbonylation and O-demethylation of 132 . When the same procedure was performed with the molecular solvent DMF using K 2 CO 3 as base, the products were only attained after 16 h at room temperature .…”
Section: Synthesis Of Six-membered Heterocyclesmentioning
confidence: 93%
See 2 more Smart Citations
“…Electrospray ionization (positive mode) mass spectra were recorded on a WATERS LCT mass spectrometer. The styrene derivatives 1b, [14] 1c, [15] 1g, [16] and 1h [15] and the Michael adducts 3a, [17] 3c, [18] 3h, [10] 3i, [10] 3j, [19] 3k, [20] and 3l [19] were prepared according to literature procedures.…”
Section: Methodsmentioning
confidence: 99%